KERUKUNAN HIDUP MASYARAKAT DALAM BINGKAI MULTIKULTURAL DI KAMPUNG MADRAS KOTA MEDAN - Dafa Rizky Prayoga; Rohani; Gindo Leontinus; Tiur Debora Ginting; Wanda Nelwita Damayani; Soedirman Z (Geography Education Study Program, Universitas Samudra, 2021)
The research is based on phenomena related to the multiculutral life of the people of Medan City, one of which is the Madras Village. The research aims to find multicultural patterns and values ​​of tolerance in the community of Kampung Madras, Medan City. The research subjects were the Tamil community in the Madras Village, Medan City. Data were collected based on primary and secondary sources. Primary sources are through direct observation, interviews with one of the oldest in Madras Village, and documentation in the form of photographs. Secondary sources through literacy of several relevant articles and journals. Descriptive data analysis by combining observation results with literature. The results of the study concluded that the people of Kampung Madras or known as Kampung Keling still maintain a high sense of tolerance and coexist harmoniously, besides that Kampung Madras has the potential to be a landmark as tourism in Medan City.